Sheikh Ahmad ibn Zaini Dahlan's Response to the Radical Shia Movement of Qaramithah: A Historical Study of the Book of Tarih Zaini al-Dini Dahlan - Syamsuri Ali (Global Writing Academica Researching & Publishing, 2023)
The purpose of this research is to find out Sheikh Ahmad ibn Zaini Dahlan's Response to the Radical Shia Movement of Qaramithah. This study is qualitative-descriptive to trace the sources of literature (library research) using the History method. The method is carried out with four activity processes: heuristics, criticism, verification and histriography. Based on the results of this study, it is known that the Shiite Qaramithah Movement received a negative response from Sheikh Ahmad ibn Zaini Dahlan, who directly accused him of being a